Upaya Meningkatkan Kemampuan Membaca Pemahaman bagi Siswa Berkesulitan Belajar Membaca Melalui Strategi KWL (Know, Want, Learned) Pada Siswa Kelas III Sekolah Dasar Negeri Muncul 02 - fitri Ayu Dimar; Widjojoko; Deni Wardana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The habit of reading in everyday life is an important thing. Students who like to read can gain information, experience new knowledge, and improve their learning abilities. At the elementary school level, students get many benefits through Indonesian subjects, especially in learning to read. By learning to read, students can improve their ability to communicate properly and correctly and improve their ability to understand the content of reading. Many ways can be done in learning to read, one of which is through reading comprehension. However, based on observations of third-grade students at SDN Muncul 02, some students had difficulty in reading comprehension. The problems experienced by some of these students can cause students to have difficulty understanding the contents of the reading and not be able to follow the lesson well. In delivering the material, the teacher uses less varied learning methods so that students become less active. The author conducted this research using a case study method with a qualitative research approach. The author obtained the data in this study by observation, interviews, tests, and documentation. The KWL (know, want, learned) strategy that the author uses as an effort to improve reading comprehension skills has undergone a much better change which can be seen from the reflection of the results of learning I and II as well as changes in student attitudes in learning. In the results of the learning process, the use of the KWL strategy has not been able to solve the existing problems. Therefore, it is still necessary to conduct learning simulation II because the ability of students who have reading difficulties has not achieved optimal results. In the results of the learning process II, using the KWL strategy, there was a better improvement in students' reading learning activities which had an impact on increasing students' reading interest and students' ability in reading comprehension. Thus, the KWL (know, want, learned) strategy can be said to be able to improve reading comprehension skills for grade III SDN 02 students who have difficulty understanding reading content because there has been a significant increase in student activity.